The Engagement of EFL Learners in Speaking Class Using WhatsApp - Abdul Halim; Wa Ode Zulhidjah Awalyah (IAIN KENDARI, 2021)
This study was conducted under qualitative design. It aimed to unveil the use of WhatsApp in engaging EFL learner in speaking class. This mode of learning did not intend to replace the face to face speaking class meeting which was done once a week. This research was used as input for the teachers to engage more students to use English after speaking class. The subjects of this study were 9 students of speaking 4 class. To obtain the data, this study used the printed WhatsApp communication and written open ended questions. This study revealed two findings: firstly, WhatsApp has helped students to speak English as indicated as follows: WhatsApp improved students’ vocabulary; feedback made in WhatsApp help students learn what is correct and incorrect; WhatsApp engaged the students with global issues which help students develop their ideas when addressing their conversation; WhatsApp could improve other language skills, such as grammar, writing, reading, and vocabulary; WhatsApp improved students’ confidence in speaking class. Secondly, the challenges faced by the students to participate actively in WhatsApp group of speaking class are: unmanaged time, assignments, and irrelevant comments. This study found that students did not really consider financial, grouping them with students who have similar interest, and use of other social media as the barrier for them to participate actively in WhatsApp group of speaking class